Disparity in low-flow trends found in snowmelt-dominated mountain rivers of western Canada - Paul H. Whitfield; John W. Pomeroy (Journal of Hydrology: Regional Studies)
Study region: A complex mountainous region that is the source of water for the major river basins of northwestern North America. Study focus: Trends in magnitudes and timing of annual low flows in relation to basin characteristics and climate indices in 106 nival rivers in British Columbia and Alberta, New hydrological insights: Two types of significant trends in annual low flows were observed: [1] decreased magnitude and earlier occurrence in the warmer southwest, or [2] increased magnitude and later occurrence in the colder, higher elevation north and east. These differences are associated with differences in the form of nival regime from the reliable cold winter and spring freshet of the north and east to regimes with fall and mid-winter melts, often associated with rainfall, in the south and west. Basin location and regional climate, rather than individual basin attributes such as elevation or hypsometry drove these differences in streamflow regimes and their responses to climate variations and warming. Atmospheric teleconnections had strong effects that corresponded to the regime and spatial differences in trends and were dominated by positive relationships between magnitude and timing with long duration indices (AMO & PDO), and negative relationships with short duration climate indices (NAO & SOI). The pattern of these relationships mimicked the temporal trends over time, positive with magnitude and timing in the northeast, and negative in the southwest.